Guaranteed Growth of Income - Eisner, Robert (Econometrica, 1953)
PROFESSOR DOMAR, several years ago, raised interesting question of whether a governmental guarantee that income would grow at full-employment equilibrium rate of growth will actually call forth sufficient private investment to generate increase in income necessary to maintain full employment [1]. This note will call attention to certain pitfalls for unwary explorers of Domar's challenging work. In Domar model, a equals increase in productive capacity of economy, s equals that increase for individual firm associated with a unit of investment, while a equals average and marginal propensity to save. Then, assuming that investment which does not depend on growth in income (via acceleration principle) is completely absent and eschewing consideration of the numerous practical questions that income guarantee would raise, Domar argues, If economy starts from equilibrium position, expected rise in income of Yac -will require investment equal to Yaals [1, see p. 145]. If a equals Domar continues, . . a mere guarantee of a rise in income (if taken seriously by investors) will actually generate enough investment and income to make guarantee good without necessarily resorting to a government deficit. But, . . if a is appreciably below s, investment will probably fall short of savings and equilibrium will be destroyed [1, see p. 146]. Now, by magnitude of investment which an expected rise in income of Yaa will require, Domar must mean aggregate of investment undertaken by each individual entrepreneur under assumptions: (1) that each entrepreneur knows (is 100% certain) that he will experience increase in demand for his products which is exactly proportionate to guaranteed increase in national income and (2) that each entrepreneur will operate under conviction (held with 100% certainty) that each unit (or dollar) of investment which he undertakes will raise his productive capacity by amount s. With these two assumptions, we may state that entrepreneurs will seek to expand productive capacity by amount Yaa but that their initial effort in this direction will involve aggregate investment of Yaals. Then, of course, if a is less than s, amount of investment forthcoming must be less than Ya and, in accordance with multiplier theory, income must fall. However, if it were appropriate to view problem on basis of these assumptions-and Domar must indeed so envisage problem